Protection of geographical indication products and sustainable agricultural development: The role of public policies - Chunyan Li; Lanqing Ge; Qi Ban; Xiaoting Song (Agricultural Economics (AGRICECON))
This research employed co-word clustering analysis to classify 62 geographical indication (GI) protection policies from 2009 to 2023 into three distinct types. Employing Sankey diagrams, we dynamically analysed the evolution of these policy tools. These insights provide valuable experiential guidance for reforming and innovating China's GI protection system and agricultural sustainable development.